An intrinsically micro-/nanostructured pollen substrate with tunable optical properties for optoelectronic applications - Hwang, Youngkyu (2022)
There is broad interest in developing photonically active substrates from naturally abundant, minimally processed materials that can help to overcome the environmental challenges of synthetic plastic substrates while also gaining inspiration from biological design principles. To date, most efforts have focused on rationally engineering the micro- and nanoscale structural properties of cellulose-based materials by tuning fibril and fiber dimensions and packing along with chemical modifications, while there is largely untapped potential to design photonically active substrates from other classes of natural materials with distinct morphological features. Herein, the fabrication of a flexible pollen-derived substrate is reported, which exhibits high transparency (>92%) and high haze (>84%) on account of the micro- and nanostructure properties of constituent pollen particles that are readily obtained from nature and require minimal extraction or processing to form the paper-like substrate based on colloidal self-assembly. Experiments and simulations confirm that the optical properties of the pollen substrate are tunable and arise from light-matter interactions with the spiky surface of pollen particles. In a proof-of-concept example, the pollen substrate is incorporated into a functional perovskite solar cell while the tunable optical properties of the intrinsically micro-/nanostructured pollen substrate can be useful for a wide range of optoelectronic applications.